The effect of yoga and aerobic exercise on children’s physical activity in rural India: a randomized controlled trial - Tarun Reddy Katapally; Jamin Patel; Sheriff Tolulope Ibrahim; Sonal Kasture; Anuradha Khadilkar; Jasmin Bhawra (PeerJ)
Purpose This study aimed to assess the impact of yoga and aerobic exercise on moderate-to-vigorous (MVPA) levels of children in rural India. Methods The study utilized secondary data from a randomized, controlled, open-labelled, single-center, two-site, parallel-group trial. The study was conducted in rural India over a 6-month period between 2018–2019. Children aged 6 to 11 years were randomized into three groups: aerobic exercise (30 minutes, 5 days/week), control (no intervention), and yoga (30 minutes, 5 days/week). MVPA was measured at baseline and at six months using the Quantification of Physical Activity in School Children and Adolescents survey adapted and validated for Indian children. Overall sample and gender-segregated data were analyzed using paired sample t-tests and one-way analysis of variance with post-hoc analyses. Findings In the overall sample (N = 151), mean MVPA (minutes/day) increased significantly in both yoga (n = 50; p < 0.001) and aerobic exercise (n = 49; p < 0.001) groups from baseline to endline. Among males, mean MVPA increased significantly from baseline to endline in all three groups, including the control group (n = 23; p = 0.005). Among females, mean MVPA increased only in the yoga group, with baseline to endline change being significant across the three groups (p = 0.005), and with the yoga group depicting greater change in comparison to the control group (p = 0.004). Conclusions Our findings suggest that both yoga and aerobic exercise can increase MVPA among rural children, with yoga being particularly beneficial for girls—a significant finding to inform culturally-appropriate active living policies to minimize the current physical activity gender gap in India. These findings can have implications for public health programs and policies not only in India but across other rural areas worldwide, where similar challenges in promoting physical activity among children may exist.